Enhancement of social skills by using multimedia interactive social skills module application among students with autism spectrum disorder - Ibrahim, Zuraida (2019)
Social skills deficits involving students with ASD hinder the development of social competence via the mainstream school environment. This is because students with ASD learning capability for social skills was behind the average expectation of their typical peers. However, they can increase their knowledge and skills with the help of assistive technology such as mobile applications. Using the existing educational material, however, was not suitable for local students due to the different cultural norm. Therefore, the purpose of this study was to develop and investigate the effect of specifically-tailored culture-based social skills modules on mobile application and paper for teaching and learning of students with ASD that integrate more comprehensive component of social skills in a single study. The social skills modules were tested using quasi-experimental study on students with ASD from National Autism Organization of Malaysia (NASOM) for 18 weeks with 1-hour intervention session per week. The study involved three groups (N=74; n1=27, n2=25, n3=22) using specifically-tailored culture-based social skills modules on mobile application and paper that were compared to a control group using existing social skills module. Social Skills Knowledge Test (SSKT) and Social Skills for ASD (SS-ASD) instruments were used to measure knowledge of social skills and social skills respectively on students with ASD. The finding indicated that specifically-tailored culture-based social skills module irrespective of media (mobile application or paper) effectively enhance social skills among students with ASD. In conclusion, integrating cultural norm into teaching and learning material for social skills will enhance social skills development and ease inclusion in a mainstream school to develop independent living in the future.